PENGARUH PENERAPAN MODEL TREFFINGER TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI IPA SMA ADABIAH 2 PADANG - Kumala Dewi, Fitri i; Zulfaneti, Zulfaneti; Yunita, Alfi (STKIP PGRI Sumbar, 2014)
ABSTRACKTThe background of the research is the researcher found that there is a studentsâ lack understanding related to the mathematical concept at XI IPA of Senior High School Adabiah 2 Padang, and the studentsâ learning outcome at that school is also low. The purpose of the research is to find out whether the understanding of mathematical concept by applying Treffinger Model is better than Conventional model at XI IPA of Senior High School Adabiah 2 Padang Year 2013/2014. Afterward, the type of the research is an experimental research. Then, the population of the research is the students at XI IPA of Senior High School Adabiah 2 Padang Year 2013/2014. Next, the technique sampling of the research is random sampling, XI IPA 5 as the experimental class and XI IPA 1 as the control class. The instruments that use are motivation checklists and the final test with indicators of concept understanding. The type of the test is essay; 5 questions, with 0,68 reliability. Thus, the result of the test is an abnormal distribution. So, the researcher decided to use Mann-Whitney test with Z = -9,69 and Ztable=-1,65 shown thatÂ Z < Ztable with 5% real level. Last, can be concluded that the studentsâ understanding of mathematical concept by implementing Treffinger Model is better than Conventional Model at XI IPA Senior High School Adabiah 2 Padang Year 2013/2014.